HPTLC METHOD DEVELOPMENT AND VALIDATION OF A SECONDARY METABOLITE – β - SITOSTEROL FROM CAESALPINIA BONDUC (LINN.) ROXB. EMEND. DANDY & EXELL. SEEDS - SHAILAJAN SUNITA; SHAH SMRUTI; SAYED NEELAM (International Journal of Pharma and Bio Sciences, 2010)
Caesalpinia bonduc (Linn.). is commonly called as latakaranj and is widely distributed throughout India. A sensitive, simple, and accurate High-Performance Thin-Layer Chromatographic method has been established for quantitation of β-sitosterol from seed powder of Caesalpinia bonduc (Linn.) collected from different regions of India as well as from Menstrowin tablets, a polyherbal formulation used against female reproductive disorder. The seed powder was extracted with Methanol and used for quantitation. The concentration of β-sitosterol was found to be 0.1134 mg/gm. in the seed powder of Caesalpinia bonduc (Linn.) collected from Mumbai which was used as a reference sample. Quantitation of β-sitosterol was also carried out for Caesalpinia bonduc (Linn.) seeds collected from different regions of India like Kutch (Gujrat), Malvan, Madhya Pradesh and Raigad and the concentrations were found to be 0.2080 mg/gm, 0.1432 mg/gm, 0.1244 mg/gm and 0.0820 mg/gm respectively. The concentration of β-sitosterol from polyherbal formulation Menstrowin (Safe Life Herbals Pvt, ltd.) was found to be 0.02 mg/gm. Quantitation was carried out on HPTLC silica gel 60 F254 pre-coated plates with the mobile phase Toluene: Ethyl Acetate: Methanol (7:1:0.5) (v/v/v). A TLC scanner set at 366nm in fluorescence / reflectance mode was used for quantitation. β-sitosterol response was linear over the range 5 µg mL-1 to 50 µg mL-1. The method was validated for linearity, precision, accuracy and robustness.